Covid-19 Outbreak, Timber Production, and Livelihoods in Nepal - Basnyat, Bijendra; Baral, Sony; Tiwari, Krishna Raj; Shrestha, Gajendra Kumar; Adhikari, Bikash; Dahal, Yajna Nath (Tribhuvan University Journal, 2020)
The study assesses the likely consequences of COVID-19 in the forest sector of Nepal, focusing on timber production and rural livelihoods. The study conducted telephone interviews along with a review of the secondary source of information and consultations. The timber production in 2020 is likely to decrease by 80% compared to previous years, resulting in a monetary loss of NRs 647.0 million. Furthermore, local community will lose 147,447 days of employment, amounting NRs 117.9 million. This will make livelihoods of the people more vulnerable. Returning of youths from abroad can further escalate biodiversity threats. Timber import is likely to increase in the country, thus impacting on local level employment opportunities. Both long-term and short-term strategies are necessary to revive the timber production and rural livelihoods, where priority should be on increasing investment in the forestry sector. However, public-sector investment is declining. Hence there is a need to expand conservation finance portfolios to incentivise rural people on timber production and achieve synergies between conservation and livelihood outcomes.